El estandarte de la Virgen de los Dolores y la princesa de Beira en la crisis del Atlántico ibérico: una devoción y una bandera para los carlistas - Andrés María Vicent (Cahiers de Civilisation Espagnole Contemporaine)
In the summer of 1835, a banner arrived at the «camp and court» of Don Carlos, a banner with an image of Our Lady of Sorrows. Immediately, the Virgin Mary, under this title, was proclaimed «generalísima» of the «royal army» of Don Carlos. In the history of this banner, there are many elements of the political culture of early Carlists. This article examines this history by underlying the political and cultural contexts in which it developed.